Value Relevance of Earnings and Book Value in Indonesian Exchange Listed Firms - Krismiaji -,; Hermala Kusumadewi (Jurusan Akuntansi Politeknik Negeri Malang, 2020)
This study investigates the value relevance of accounting information on manufacturing companies listed on the IDX for 2012-2017. This study uses the accounting-based Ohlson's (1995) model, which includes earnings (EPS) and book value (BVS) as variables. This study shows a direct relationship between financial statements and firm value. The value relevance does not increase, yet both the value relevance for EPS and BVS, although in specific years, does. The results show that individual BVS decreases with a better amount than EPS from 2012 to 2015. Meanwhile, in 2016-2017 BVS value decreased below EPS value. Abstrak Penelitian ini menginvestigasi relevansi nilai informasi akuntansi pada perusahaan manufaktur yang terdaftar di BEI tahun 2012-2017. Model Ohlson (1995) berbasis akuntansi yang mencakup laba (EPS) dan nilai buku (BVS) sebagai variabel digunakan dalam penelitian ini. Studi ini menunjukkan adanya hubungan langsung antara laporan keuangan dan nilai perusahaan. Relevansi nilai pada perusahaan yang diteliti tidak meningkat, baik relevansi nilai EPS maupun BVS, walaupun pada tahun tertentu naik. Hasil analisis menunjukkan bahwa nilai BVS menurun secara individual dengan besaran yang lebih baik dibanding EPS tahun 2012-2015, namun tahun 2016 dan 2017 besaran nilai BVS menurun di bawah besaran nilai EPS.